Transfer Learning:Approaches and Methodologies - Barik, Swati Sucharita; Garanayak, Mamata; Nayak, Sasmita Kumari (International Journal of Computer Sciences and Engineering, 2019)
Machine learning and Data Mining Techniques are mainly used for many Real world problems. The traditional methods include training the data and test .But it will not be applicable for real world scenario. Some of the reason may be the cost of training data and inability to get those. These drawbacks are giving rise to the concept known as Transfer Learning.It ensures that training data must be independent and distributed identically.Transfer Learning is considered as a solution to the insufficient training data.